Wired for Fear: Recognizing and Countering Implicit Bias in the Brain - Roozeboom, William D. (Journal of pastoral theology, 2021)
This essay explores the connections between fear, implicit bias, and injustice, noting how the brain’s deeply embedded structures and processes for survival predispose us to detect threat. It further illustrates how the brain’s categorization processes collude with bias to favor ‘in-group’ members and ‘other’ ‘out-group’ members. Taken together, these factors limit the brain’s mirror neural network’s capacities to empathize across lines of difference. While this sounds reductionistic and pessimistic, the good news is that, just like the brain is generally malleable, implicit biases can be modified through debiasing practices. In exploring these concepts, the essay examines the contributions from intercultural and postcolonial pastoral and practical theology to provide constructive frameworks for facing one another, enhancing recognition, and developing neighbor-love.